Stabilizing Fragile States : Why It Matters and What to Do about It - Phillips, Rufus C. (Book collections on Project MUSE., 2022)
"Stabilizing Fragile States is about intervening to help fragile states stabilize in the face of internal challenges that threaten national security and how the United States can do better at less cost with improved chances of success. Recent US involvements have ranged in intensity and size from Colombia, which did not put American boots on the ground, to massive interventions in Iraq and Afghanistan, which did. The lack of success in Afghanistan and Iraq has tended to dominate the national conversation about dealing with fragile states. Helping stabilize fragile states has been too much of a poorly informed, impersonal, technocratic and conflicted process, dominated by reactions to events and missing a more human approach tailored to various countries' circumstances. In this book, Rufus Phillips explains why we have not been more successful and what it would take to make this form of foreign intervention effective and sustainable"--